Novel biodegradable laminarin microparticles for biomedical applications - Castanheira, Edgar J. (2020)
Fabrication of biocompatible polymeric carriers for a sustained/controlled drug-delivery have been extensively explored over the years. Furthermore, systems based on polymers from natural origins exceed conventional polymers in biocompatibility, biodegradability and cost efficiency. Polysaccharides are one of the most common biopolymers found in nature and they can achieve a high degree of complexity and fine biological properties. Herein, is proposed a biodegradable and biocompatible microcarrier synthesized from laminarin, a low Mw marine polysaccharide based on glucose units with a great biological activity, such as, immune modulation and antimicrobial properties. Within this work, controlled size microparticles were obtained from novel modifications of laminarin. Microparticles shown 40% release of fluorescein isothiocyanate-dextran (70 kDa) after 24 h and full degradability after 11 days, when in physiological conditions. When incubated with human adipose stem and L929 cell lines (up to a microparticle concentration of 100 µg/mL) no cytotoxicity was perceived, and neither membrane or nucleus disturbance. Thus, microparticles synthesized from laminarin, proved to be a cost efficient, biocompatible and biodegradable system.